2013
DOI: 10.1002/jgrg.20056
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm to assess gross primary production for terrestrial ecosystems from MODIS imagery

Abstract: [1] Quantifying carbon fluxes at large spatial scales has attracted considerable scientific attentions. In this study, a novel approach was proposed to estimate the terrestrial ecosystem gross primary production (GPP) using imagery from the satellite-borne Moderate Resolution Imaging Spectroradiometer (MODIS) sensor. The new model (named Temperature and Greenness Rectangle, TGR) uses a combination of MODIS Enhanced Vegetation Index and Land Surface Temperature products as well as in situ measurement of photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 79 publications
0
43
0
7
Order By: Relevance
“…The water stress on LUE (i.e., fw) had been characterized by air moisture condition (i.e., VPD s ) and/or soil water content (i.e., W s ), or via land water index (i.e., WI) that can reflect the vegetation water stress in different LUE models, yet there were controversies on which one was optimal (Medlyn, 2011;Hashimoto et al, 2013;Yang et al, 2013). Coincidently, both EC-LUE and VPM, the two better-performed LUE models, used WI.…”
Section: Comparisons Of the Methods To Define Water Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The water stress on LUE (i.e., fw) had been characterized by air moisture condition (i.e., VPD s ) and/or soil water content (i.e., W s ), or via land water index (i.e., WI) that can reflect the vegetation water stress in different LUE models, yet there were controversies on which one was optimal (Medlyn, 2011;Hashimoto et al, 2013;Yang et al, 2013). Coincidently, both EC-LUE and VPM, the two better-performed LUE models, used WI.…”
Section: Comparisons Of the Methods To Define Water Stressmentioning
confidence: 99%
“…The higher accuracies of EC-LUE, GLO-PEM, and VPM than CASA indicated that all these three models might be robust in estimating ecosystem GPP over large areas. However, it would be better if with briefer model structure and fewer input variables without sacrificing of model accuracy (Goetz et al, 1999;Yang et al, 2013). Among those three models, the water stress expression (i.e., fw) in GLO-PEM (Eq.…”
Section: Comparisons Of the Four Lue Models In Estimating Gppmentioning
confidence: 99%
See 1 more Smart Citation
“…While VPM uses LSWI to determine the effect of water stress, some studies used other ancillary data or variables like LST, actual and potential evapotranspiration (AET and PET) to improve the LUE parameter (Maselli, Papale, Puletti, Chirici, & Corona, 2009;Moreno et al, 2012;Yang, Shang, Guan, & Jiang, 2013). The use of LSWI is convenient as the data are available from MODIS and Landsat.…”
Section: Trade-off Between Comprehensiveness and Applicability In Satmentioning
confidence: 99%
“…Among a variety of PEMs (Cramer et al, 1999;Wu et al, 2010;Yang et al, 2013), we employed the MOD17 model (Running et al, 2004) developed by the Numerical Terradynamic Simulation Group (NTSG) at the University of Montana (UMT). The MOD17 model is used to provide GPP/NPP estimates from MODIS data at 8-day and yearly time steps.…”
Section: The Modis Gpp (Mod17) Modelmentioning
confidence: 99%